The Health-promoting Potential of Edible Mushroom Proteins - Sousa, Ana Sofia; Araújo-Rodrigues, Helena; Pintado, Manuela Estevez (Current pharmaceutical design, 2023)
Edible mushrooms have been classified as "next-generation food" due to their high nutritional value coupled with their biological and functional potential. The most extensively studied and reported mushroom macromolecules are polysaccharides. However, macrofungi proteins and peptides are also a representative and significant bioactive group. Several factors such as species, substrate composition and harvest time significantly impact the mushroom protein content, typically ranging between 19 and 35% on a dry weight basis. Proteins work based on their shape and structure. Numerous extraction methods, including chemical and non-conventional, and their implications on protein yield and stability will be discussed. Beyond their biological potential, a great advantage of mushroom proteins is their uniqueness, as they often differ from animal, vegetable, and microbial proteins. According to recently published reports, the most relevant mushroom bioactive proteins and peptides include lectins, fungal immunomodulatory proteins, ubiquitin-like proteins, and proteins possessing enzymatic activity such as ribonucleases laccases, and other enzymes and ergothioneine. These are reported as antioxidant, antiviral, antifungal, antibacterial, antihypertensive, immunomodulatory, antitumour, antihypercholesterolemic or antihyperlipidemic, antidiabetic and anti-inflammatory properties, which improved proteins and peptides research interest and contributed to the increase of mushroom market value. This review provides an overview of the most relevant biochemical and biological properties of the main protein groups in edible mushrooms, explicitly focusing on their biomedical potential. Although mushrooms are a rich source of various proteins, many of these molecules have yet to be identified and characterised. Accordingly, it is crucial to identify and characterise new macromolecules of macrofungi origin, which opens an opportunity for further investigation to identify new bioactives for food, nutraceutical, or medicinal applications.